Acute Gastric Dilatation due to Pyloric Band, with Acute Appendicitis and IleoIleal Intussusception in a 4-Year-Old Girl: Case Report - Ida Ayu Diah WEDAWATI; Putu Windhu MAHAYANA; I Gede Putu Wegen WISMAYA; Made Dwi Yoga BHARATA (International Journal of Environmental, Sustainability, and Social Science, 2022)
Acute gastric dilatation (AGD) is caused by mechanical and non-mechanical stomach processes. Acute appendicitis affects children and is treated with surgery. Intussusception is proximal bowel invagination against the distal bowel. Clinical findings of intussusception in the form of intermittent abdominal pain, a palpable mass in the abdomen, accompanied by wine-red stools. Due to significant morbidity and mortality, multiple-problem surgical emergencies require accurate diagnosis and treatment. A 4-year-old girl complained of a full stomach, abdominal discomfort, inability to flatus, vomiting, and fever, suggesting appendix perforation and widespread peritonitis. Radiographs show an intra-abdominal mass. Exploratory laparotomy surgery revealed gastric dilatation due to the pyloric band, acute appendicitis, ileoileal intussusception, grade 3 adhesions, and generalized peritonitis. Laparoscopic surgery revealed significant issues. The procedure was followed by partial gastrectomy, milking procedures, appendectomy, omentectomy and release of adhesions. Gastric histopathological examination showed the results of acute suppurative gastritis. Postoperatively the patient was hospitalized for nine days with improved condition. The complex pathogenesis is related to multiple cases in these patients. A continuous process is thought to occur between acute appendicitis and ER through the mechanism of intra-abdominal infection involving the omentum according to the anatomical location. Then hypertrophy of the lymphoid tissue of Peyer's plaque due to acute appendicitis is thought to contribute to intussusception. Clinical evaluation and appropriate management of surgical emergency cases with multiple problems are important to prevent further deterioration and complications.